Exploring Human Resource Competence and Management Performance of a Village-Owned Enterprise - Putri Nugrahaningsih; Andi Asrihapsari; Vidia Ayu Satyanovi; Labbaika Dwi Ayu Rahmawati; Denty Arista; Lina Nur Ardila (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2022)
This study aims at investigating the competence of human resources of BUMDes Blulukan in managing the business that leads to green entrepreneurship. This study uses a qualitative descriptive method using interviews and questionnaires as a data collection technique The conclusion of the study shows that the human resources in the BUMDes have adequate competence and level of understanding on green entrepreneurship, as seen from the effort in managing waste by creating products with higher selling points to improve the village communities' welfare in yielding innovative products from waste and generating income for village community products with high-selling values. AbstrakTujuan penelitian ini adalah melihat kemampuan Sumber Daya Manusia studi kasus pada BUMDES Blulukan dalam mengelola bisnis yang mengarah kepada green entrepreneurship. Penelitian ini menggunakan metode deskriptif kualitatif dengan cara wawancara dan penyebaran kuesioner sebagai teknik pengumpulan datanya. Kesimpulan penelitian menunjukkan bahwa kemampuan dan tingkat pemahaman SDM BUMDES terkait green entrepreneurship sudah cukup baik dengan melakukan pemanfaatan pengelolaan sampah menjadi nilai jual yang dapat meningkatkan kesejahteraan desa pada produk inovasi berupa pemanfaatan limbah sampah yang sebelumnya menjadi keresahan desa diolah menjadi produk yang menghasilkan nilai jual.